Perancangan Bisnis Untuk Produk Teh Bunga "Beautea" - Alyssa Dewi; Rendy Iswanto (Jurnal Vicidi, 2019)
Too much activity and work tend to make us forget to rest. Tea has been known for generations for its antioxidant content and relaxation properties. A study in Taiwan with 80 postnatal women suffering from sleep deprivation shows that the consumption of Chamomile flower tea may help increase the quality of sleep and reduce the symptoms of depression. Human adults need at least 7 hours of quality sleep. If we fulfill the amount of sleep our body needs, we may notice less wrinkles, obscured dark circles, denser hair, healthier appearance, and even improves the absorption of product by our system. Beautea offers flower tea that may help women relax and achieve their true beauty potential. The purpose of this journal is to develop and research the product “Beautea” to understand public’s awareness about flower tea and plan on strategy that matches the product. The research is done by observing marketing strategy of similar businesses to understand the interest of target audience towards the offered products. This journal is supported by field data as primary source and references as secondary sources such as books and journals which undergo observations, expert and extreme user interviews, and online and offline questioner.